Major Issues of Care in Thalassemia Major Children Refugees. Issue 8 (November 2019) - Hamouni, Eglantine; Armari, Corinne; Dupuis, Clémentine; Giroux-Lathuile, Claudine; Petit, Audrey; Plantaz, Dominique; Adjaoud, Dalila; Rubio, Amandine
Abstract : Beta thalassemia major (βTM) is the most common inherited hemoglobinopathy. Management essentially focuses on preventing and treating complications. Conventional treatment is based on a regular blood transfusion program, and chelation therapy. Management essentially focuses on preventing and treating complications. Severe complications of βTM are very rarely seen in children in Europe. In the context of the migrant crisis, pediatricians will be confronted with the challenge of managing severe complicated βTM. We report the case of 2 Syrian 10-year-old twin girls who arrived to France with numerous and severe complications of βTM: hemochromatosis, alloimmunization, hypopituitarism, osteopenia… Their clinical management, which led to successful vital and functional improvement, is reported in this article.